A escolarização no município de Corbélia (PR): 1955 – 1982. - Vitali, Ana Paula (2022)
This study discusses the theme of the History of Education in the Western Paraná, more specifically in the municipality of Corbélia (PR). Entitled The schooling in the municipality of Corbélia (PR), 1955 to 1982, it aims to understand the historical process of schooling from its economic, social, political and cultural determinants. It took into consideration the historical course about the creation of the first schools until the effective implementation of public education and its operation. We also approached the emergence of the first school institutions that contributed to the local schooling process, in line with the phenomenon of opening and closing of schools. The research is based on the bibliographical study and on documentary research, such as: school minutes, iconographic sources, federal, state and municipal legislation related to the research theme. Sources were collected from the archives of the City Hall, the Town Hall, the Municipal Secretary of Education, the Municipal Museum, the Archives of Municipal and State Schools, the Documentation Sector of the Regional Education Center of Cascavel, the collection of the Museum of Image and Sound of Cascavel and the archives of the Franciscan Sisters' House of Corbélia.